NANO ANTIBACTERIAL LIQUID SOAP FORMULATION BASED ON NYAMPLUNG SEED OIL WITH ACTIVE INGREDIENTS METHANOL EXTRACT OF KETAPANG FRUIT - Chasani, Mochammad; Riyani, Kapti; Setyaningtyas, Tien; Putri, Prima Dwi Rahma; Saputra, Dimas (Indonesian Journal of Pure and Applied Chemistry, 2025)
The development of science and technology in cosmetics is shifting towards a natural approach, utilizing natural ingredients with potential benefits. Nyamplung seed oil is an abundant, non-edible oil that contains fatty acid chains with the potential to serve as a base for soap. The optimization of the soap effect is achieved through a nanoformulation using the sonication method to enhance sound delivery. The objective of this study is to produce soap products from a methanol extract of Ketapang flesh with the best characteristics according to SNI and to determine the effect of a liquid soap nanoformula on antibacterial activity. The results of the study showed that SA1 (a 1% methanol extract of Ketapang flesh) is a liquid soap with the best characteristics according to the SNI. The characterization results are as follows: pH 9.185, density 1.0212 g/mL, total fatty acid percentage 66.93%, neutral fatty acids 3.5356%, free fat 2.2533%, and foam stability 88.50%. The antibacterial activity of liquid soap (SA1) of nanoformula was higher than that of non-nano with an inhibition zone against Staphylococcus aureus of 19.97 mm and 18.04 mm.